The Effect of Mind Mapping-Assisted Problem-Based Learning (PBL) Model on Science Process Skills of Fifth Graders - Anratriningrum, Rifka Ayu; Edy Mulyono, Sungkowo (Journal of Primary Education, 2020)
Science learning model directs students to learn concept understanding and scientific principle. Scientific principle in science learning relate to investigation or experiment to drill science process skills that can develop critical thinking and problem-solving abilities. Process skills are students' abilities to manage what has been gained in teaching and learning activities. The purpose of this study was to analyze the effect of using the Mind Mapping, Problem Based Learning (PBL) model, and Problem Based Learning model assisted by Mind Mapping on students' science process skills. The research method used quantitative research in the form of quasi experimental design. The sample of this study were students of 5th grade with 30 students as experimental class, 24 students as control-1 class, and 28 students as control-2 class. The data collection techniques used in this study were written test, observation, and documentation. The results of the analysis showed that simultaneously a learning model affected students' science process skills by 13%. This study had also showed that of the three models that had been used, problem-based learning assisted by mind mapping model was the most effective model for improving students' science process skills compared to problem-based learning model or mind mapping model